Immunogenicity of 2-dose pre-exposure rabies vaccine co-administered with quadrivalent influenza vaccine in children - Napaporn Chantasrisawad (Elsevier, 2021)
Objectives: The World Health Organization recommends a 2-dose rabies pre-exposure prophylaxis (PrEP) regimen. This study aimed to compare the immunogenicity of rabies PrEP regimens co-administered with inactivated quadrivalent influenza vaccine (IIV4). Methods: Children aged 3 to 9 years were randomly assigned (2:2:1) to receive 0.25 mL of chromatographically purified Vero cell rabies vaccine intramuscularly: Group A at day 0, 7 with IIV4; Group B at day 0, 28 with IIV4; Group C at day 0, 7. A booster-dose of CPRV was given on day 365. Primary outcome was the proportion of children with protective rabies virus neutralizing antibody (RVNA) ≥ 0.5 IU/mL, on day 42 and 7 days post-booster. Results: From November 2019 to January 2020; 100 children with a median age (IQR) of 5.4 years (4.8-7.3) were enrolled. All participants achieved protective RVNA titers on day 42 and 7-days post booster. Geometric mean titers (GMT) at day 42 were Group A, 8.98(95%CI 7.06-11.42); Group B, 23.89(95%CI 19.33-29.51); Group C, 9.94(95%CI 7.03-14.06). Likewise, RVNA GMT at 7 days post-booster were Group A, 42.53(95%CI 18.41-66.64); Group B, 23.19(95%CI 17.28-29.10); Group C, 57.75 (95%CI 35.86-79.67). Conclusions: The 2-dose PrEP regimen of rabies vaccine produces adequate immune response either 0,7 or 0, 28 regimens.